2013
DOI: 10.1371/journal.pone.0081413
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Neuropathy Can Be Induced by High Fat Diet In Vivo and Palmitic Acid Exposure In Vitro

Abstract: ObjectiveObese and/or diabetic patients have elevated levels of free fatty acids and increased susceptibility to gastrointestinal symptoms. Since the enteric nervous system is pivotal in regulating gastrointestinal functions alterations or neuropathy in the enteric neurons are suspected to occur in these conditions. Lipid induced intestinal changes, in particular on enteric neurons, were investigated in vitro and in vivo using primary cell culture and a high fat diet (HFD) mouse model.DesignMice were fed norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 41 publications
10
80
0
1
Order By: Relevance
“…It is also notable that the P2Y 13 −/− mice fed with ND displayed an even higher number of neurons per millimetre section in colon compared with ND-fed P2Y 13 +/+ littermates. The finding that PA induces loss of myenteric neurons from P2Y 13 +/+ mice in vitro is well in line with previous findings, describing PA-induced loss of cultured myenteric neurons from rat [22]. The current study also shows that cultured myenteric neurons from P2Y 13 −/− mice are resistant to PAinduced loss.…”
Section: Lipid-induced Neuronal Losssupporting
confidence: 93%
See 4 more Smart Citations
“…It is also notable that the P2Y 13 −/− mice fed with ND displayed an even higher number of neurons per millimetre section in colon compared with ND-fed P2Y 13 +/+ littermates. The finding that PA induces loss of myenteric neurons from P2Y 13 +/+ mice in vitro is well in line with previous findings, describing PA-induced loss of cultured myenteric neurons from rat [22]. The current study also shows that cultured myenteric neurons from P2Y 13 −/− mice are resistant to PAinduced loss.…”
Section: Lipid-induced Neuronal Losssupporting
confidence: 93%
“…The study confirmed previous findings on HFD-fed C57BL/6 mice [22], in that HFD induced a significant loss of myenteric neurons in both the ileum and colon in the P2Y 13 +/+ mice. Surprisingly, the P2Y 13 −/− mice showed a remarkable protection against HFD-induced neuronal loss.…”
Section: Lipid-induced Neuronal Losssupporting
confidence: 91%
See 3 more Smart Citations